Position Of Plurality Of Creditors And Holders Of Right In Law And Fiqh (Islamic Jurisprudence) - Safaei, Seyyed Hossein; Abdollahi, Aref (The Turkish Online Journal of Design Art and Communication, 2016)
Plurality of creditors and holders of right is as one of the removal of obligation examined and analyzed both in internal law and foreign law that each of creditors and holders of right can demand the debtor to full discharge of debt entirely. Plurality of creditors in reality is a complex commitment including numerous parties. In contrast, simplex and comprehensive obligations being without foreign stipulations - whether its origin is contractual or out of contract, that anyway creditors - whether on individual due and or on resolvable and joint due, will be claimed independently- in the extent of portion and share of the own owner and by receiving the debt, the debtor will be cleared from obligation.
Keywords: Plurality of creditors; Holders of right; inheritance; permission